Penatalaksanaan Holistik Pasien Anak Usia 5 Tahun Dengan Tb Paru Melalui Pendekatan Dokter Keluarga Di Wilayah Puskesmas - Alkautsar, Ahmad; Zuraida, Reni (Medula, 2024)
Tuberculosis cases in children at 2022 reach 1.1 million in the world and 100,726 cases in Indonesia. Management of Tuberculosis in children needs holistic treatment with a family doctor approach to achieve Tuberculosis elimination targets. The aim of this study is  to apply the principles of family medicine services to patients  and carry out holistic management based on the patient problem found with patient-centered approach, family focused, and community oriented based on Evidence Based Medicine. This study is a case report with Primary data obtained through history taking, physical examination and home visits to complete family, psychosocial and environmental data. Secondary data was obtained from the patient's medical record. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study. Diet and health behavior of patients classified as lacking. Knowledge about Tuberculosis disease and the implementation of healthy behavior in the family still poorly. After the intervention, there was an improvement in the diet and the patients diet behavior. Then there is an increase in knowledge through pretest and posttest as well as improvement in family life patterns to become healthier.  After holistic management was carried out based on the problems identified through family doctor approach, there was an increase in knowledge, nutritional intake, and better healthy behavior.